The Privatization of the Russian Coal Industry : Policies and Processes in the Transformation of a Major Industry - Artemiev, Igor (World Bank, Washington, DC, 2014)
This paper provides an overview of the privatization of the Russian coal industry. It reviews the salient aspects of the Government's privatization policy as it evolved over the years, and looks at the reasons for the successes and the pitfalls encountered along the way. Specific procedures and methods of sale are described in detail. A profile of the new owners of the industry is given, with a look at the implications for competition in the industry and at first performance indicators. As the World Bank has been closely involved in the support of the Government's coal sector restructuring program through provision of financing and policy advice, throughout the paper aspects of World Bank advice are considered.